Teachers' Perspectives and Institutional Readiness in the Implementation of Holistic Islamic Education: A Case from Negeri Sembilan, Malaysia - Budiman, Septian Arief; Mukhlisin, Mukhlisin; Isnaeni, Fil; Hadi, Sopyan; Othman, Mohd Fuad (Gemilang Maju Publikasi Ilmiah (GMPI), 2025)
This study explores the implementation of holistic Islamic education among secondary students at Sheikh Haji Mohd Said National Religious Secondary School, Negeri Sembilan, Malaysia. Holistic Islamic education promotes the integrated development of spiritual, intellectual, emotional, and social aspects to foster balanced individuals. Employing a qualitative case study approach, data were gathered through semi-structured interviews with six teachers, classroom observations over six weeks, and curriculum document analysis. Findings reveal that although the curriculum reflects the principles of holistic education, implementation varies due to limited resources, time constraints, and differences in teacher preparedness. Nonetheless, the approach positively influences students’ character, religious understanding, and social behavior. The study concludes that teacher capacity-building, infrastructural improvement, and community involvement are essential to strengthen holistic education practices. These findings contribute to the discourse on holistic Islamic education in Malaysia and offer practical recommendations for educators and policymakers aiming to promote balanced student development.